Temporal Validation of a Predictive Score for Death in Children with Visceral Leishmaniasis. (22nd December 2021) - Foinquinos, Juliana; Duarte, Maria do Carmo; Figueiroa, Jose Natal; Correia, Jailson B.; Cavalcanti, Nara Vasconcelos
Abstract : Objectives . To perform a temporal validation of a predictive model for death in children with visceral leishmaniasis (VL). Methods . A temporal validation of a children-exclusive predictive model of death due to VL (Sampaio et al. 2010 model), using a retrospective cohort, hereby called validation cohort. The validation cohort convenience sample was made of 156 patients less than 15 years old hospitalized between 2008 and 2018 with VL. Patients included in the Sampaio et al. 2010 study are here denominated derivation cohort, which was composed of 546 patients hospitalized in the same hospital setting in the period from 1996 to 2006. The calibration and discriminative capacity of the model to predict death by VL in the validation cohort were then assessed through the procedure of logistic recalibration that readjusted its coefficients. The calibration of the updated model was tested using Hosmer–Lemeshow test and Spiegelhalter test. A ROC curve was built and the value of the area under this curve represented the model's discrimination. Results . The validation cohort found a lethality of 6.4%. The Sampaio et al. 2010 model demonstrated inadequate calibration in the validation cohort (Spiegelhalter test: p = 0.007 ). It also presented unsatisfactory discriminative capacity, evaluated by the area under the ROC curve = 0.618. After the coefficient readjustment, the model showed adequate calibration (Spiegelhalter test, p = 0.988 ) and better discrimination, becoming satisfactory (AUROC = 0.762). The score developed by Sampaio et al. 2010 attributed 1 point to the variables dyspnea, associated infections, and neutrophil count <500/mm 3 ; 2 points to jaundice and mucosal bleeding; and 3 points to platelet count <50, 000/mm 3 . In the recalibrated model, each one of the variables had a scoring of 1 point for each. Conclusion . The temporally validated model, after coefficient readjustment, presented adequate calibration and discrimination to predict death in children hospitalized with VL.